2011
DOI: 10.1088/0953-8984/23/20/206006
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption study of the local order around Mn in Mn:ZnO thin films: the role of vacancies and structural distortions

Abstract: Abstract.This work reports an X-ray absorption near-edge structure spectroscopy (XANES) study at both Mn and Zn K-edge in Zn 0.95 Mn 0.05 O thin films prepared with different sputtering gases (pure Ar, Ar/N 2 and Ar/O 2 ). We have studied the local order around Mn in the films, with special emphasis in the role played by both oxygen and zinc vacancies and by the structural distortion associated with the substitution of Zn by Mn in the ZnO host. Our results indicate that the dependence of the magnetic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 35 publications
10
37
0
Order By: Relevance
“…[44][45][46] We have found that the best reproduction of the experimental data is obtained by using an overlapping factor of 10% and the real Dirac-Hara ECP potential, in agreement to previous works. 47,48 As shown in the top panel of Fig. 9 we have first verified that the computations are able of reproducing the characteristic spectral features of the different polymorphs as reported in Fig.…”
Section: Ab Initio Xanes Calculationssupporting
confidence: 67%
“…[44][45][46] We have found that the best reproduction of the experimental data is obtained by using an overlapping factor of 10% and the real Dirac-Hara ECP potential, in agreement to previous works. 47,48 As shown in the top panel of Fig. 9 we have first verified that the computations are able of reproducing the characteristic spectral features of the different polymorphs as reported in Fig.…”
Section: Ab Initio Xanes Calculationssupporting
confidence: 67%
“…During these calculations we have tested the performance of different exchange and correlation potentials (ECP) to account for the experimental spectrum. We have found that the best agreement between the computations and the experimental spectrum is obtained by using an overlapping factor of 1% and the Dirac-Hara ECP potential, in agreement with previous works for transition metal oxides (Guglieri & Chaboy, 2010;Guglieri et al, 2011).…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, there has been no investigation on the symmetry of Zn atoms in ternary Ni 1−x Zn x O cubic RS solid solutions using the near edge X-ray absorption spectroscopy (XANES) technique, which is the widely accepted technique for determining the symmetry of the substituted atoms in ternary solid solutions 15,16. 14 However, there are no experimental data available in the Zn composition range of 0 ≤ x ≤ 0.30 in which single phase ternary Ni 1−x Zn x O cubic RS solid solutions are realized under normal conditions.…”
mentioning
confidence: 99%